Is Creative Description Always Effective in Purchase Intention? The Construal Level Theory as a Moderating Effect - Yao, Fei-Si; Shao, Jing-Bo; Zhang, He (Frontiers in Psychology, 2021)
Online shopping has witnessed rapid growth in recent times. This paper draws from the construal level theory to examine the divergent effects of creative text descriptions of products on consumers’ purchase intention in the online context. It also investigates consumers’ construal level and its moderating role in this relationship. It assumes that creative description embraces more rhetorical devices with analogies. In so doing, such texts demand a more abstract, top-down, flexible mindset from consumers, which makes it more persuasive to some consumers with high-level construal. This study’s evidence comes from three experiments. These results suggest that creative text descriptions are generally more persuasive than noncreative ones in the online context, and that the persuasiveness of creative descriptions can be accentuated (vs. attenuated) especially for high- (vs. low-) level construal individuals. The findings hold various theoretical implications for creative marketing messages and construal level theory. First, the current research broadens and integrates relevant research by exploring the creative language in the online context. Also, it demonstrates that construal level—that is, consumers’ internal thoughts, rather than external factors—influences their preference for creative description style, thus helping extend the applications of construal level theory to the field of creative marketing communications and integrate the research discoveries in metaphor communication.